Measuring children’s values from around the world: Cross-cultural adaptations of the Picture-Based Value Survey for Children (PBVS-C) - Döring, Anna K. (Studia Psychologica: Theoria et praxis, 2018)
The Picture-Based Value Survey for Children (PBVS-C; Döring et al., 2010) assesses children’s values through self-report and thereby depicts Schwartz’s theory of universal human values at an early age (approximately six to eleven years). Recently, the original German version has been adapted for application in Poland, Bulgaria, the Ukraine, France, Italy, Switzerland, the UK, New Zealand, Australia, the USA, Brazil, Turkey, Israel, and Estonia, and it is currently adapted for application in Ireland, Russia, and Portugal. In this manuscript, we accompany the PBVS-C on its journey around the world and systematically explore culture-specifics in the adaptation process with a particular focus on the meaning of the value pictures, as the PBVS-C’s core elements. Integrating findings from these adaptations of the PBVS-C, we aim to share best practice and draw a roadmap for future adaptations in other cultures. This article further serves as a resource to locate existing studies with the PBVS-C.